{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

test3 - ½ Ö Ø Ð ÔÓ ÒØ× Ó Ø ÙÒ Ø ÓÒ f(x y...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ½ Ö Ø Ð ÔÓ ÒØ× Ó Ø ÙÒ Ø ÓÒ f (x, y ) = (x − 3)(x − y ) Ò Ð ×× Ý ÓØ Ñ× Ñ Ü ÑÙѸ ÐÓ Ð Ñ Ò ÑÙѸ ÓÖ × Ð ÔÓ Òغ 2 2 ÑÖ× Ò ÐÐ Ø ÐÓ Ð fx = x2 − y 2 + (x − 3)(2x) = 3x2 − y 2 − 6x Ö Ø Ð ÔÓ ÒØ× Ö ×ÓÐÙØ ÓÒ× Ó 3x2 − y2 − 6x = 0, −2xy + 6y = 0. ÖÓÑ Ø × ÓÒ ÕÙ Ø ÓÒ −2y(x − 3) = 0 Û Ø y = 0 ÓÖ x = 3. Á y = 0 Ø Ò Ø Ö×Ø ÕÙ Ø ÓÒ Ú × 3x(x − 2) = 0, x1 = 0, x2 = 2 Ò P1(0, 0) Ò P2 (2, 0) Ö Ö Ø Ð ÔÓ ÒØ׺ Á x = 3 Ø Ò Ø Ö×Ø ÕÙ Ø ÓÒ Ú × 27 − y2 − 18 = 0, y2 = 9, y = ±3 Ò Ø ÓØ Ö Ö Ø Ð ÔÓ ÒØ× Ö P3(3, 3), P4(3, −3). ÆÓÛ fxx = 6x − 6, fxy = −2y, fyy = −2x + 6 2 Ò ∆ = fxxfyy − fxy = (6x − 6)(−2x +6) − 4y2 = −12(x − 1)(x − 3) − 4y2 ∆(P1 ) < 0 ⇒ P1 × × Ð ÔÓ Òغ ∆(P2 ) > 0, fxx (P2 ) > 0 ⇒ P2 × Ñ Ò ÑÙѺ ∆(P3 ) < 0, ∆(P4 ) < 0 ⇒ P3 Ò P4 Ö × Ð ÔÓ ÒØ׺ ¾ Ñ Ö × ËÙÔÔÓ× Ø Ú ÐÓ ØÝ Ð Ó Ù × ÚÒ Ý F = xi + z j ´ Ò Ñ»× µº Ä Ø S Ø ØÖ Ò Ð Û Ø Ú ÖØ × (1, 0, 0), (0, 2, 0), (0, 0, 2). ÀÓÛ Ñ ÒÝ Ù Ñ Ø Ö× Ó Ù Ô Ö × ÓÒ Ö ÖÓ×× Ò Ø ×ÙÖ S ÒØ Ö Ø ÓÒ Ó Ø ÙÔÛ Ö ÒÓÖÑ Ð n ØÓ S ´Ê ÐÐ Ø Ø Ø ÙÜ Ó F ÖÓ×× S × S F · ndS µ fy = (x − 3)(−2y ) = −2xy + 6y Ì z=0Û Ø y = 2 − 2x, ×Ó Ý ´ º¾¿µ Ò ÝÓÙÖ Ø ÜØ ÐÙÜ|S = F · ndS = (x, −2x − y + 2, 0)(2, 1, 1)dA = S W 2 1 2−2x 1 =00 (2x − 2x − y + 2dydx) = 0 (− y2 + 2y )|2−2x dx = 0 1 1 1 2 2 = 0 (−2(1 − x) ) + 4(1 − x)dx = 2 0 (1 − x )dx = 2 0 (1 − x2 )dx = 3 = 2[x − x ]1 = 4 Ñ3 /× 30 3 4(x − 1) + 2y + 2z = 0) ÕÙ Ø ÓÒ Ó Ø ÔÐ Ò Ø ÖÓÙ Ø ¿ Ú Ò ÔÓ ÒØ× × z = −2x − y + 2 (N = (−1, 2, 0) × (−1, 0, 2) = (4, 2, 2) Ò P0 = (1, 0, 0) ×Ó ÓÖ ½ ¿´ µ ¿ Ñ Ö × ÓÖÑÙÐ Ø Ø ××ÙÑÔØ ÓÒ׺ ÚÖ Ò Ì ÓÖ Ñ Ò ÐÐ Ó Ø× Á V × Ö ÙÐ Ö Ö ÓÒ Ò R3 Û Ø Ô Û × ×ÑÓÓØ ÓÙÒ ÖÝ ∂V, ÓÖ ÒØ ×Ó Ø Ø Ø ÔÓ× Ø Ú ÒÓÖÑ Ð ÔÓ ÒØ× ÓÙØ Ó V, Ò F × Ú ØÓÖ Ð Ó Ð ×× C 1(V ), Ø Ò F · ndS = ∂V V div FdV ´µ Ñ Ö × Ú ÐÙ Ø F · n dS F = xi + 1 y j + z k 4 S Û Ö S ×Ø ÓÑÔÐ Ø ÓÙÒ ÖÝ Ó Ö ÓÒ V = {(x, y, z ) : x2 + 1 y 2 + z 2 ≤ 1, z ≥ 0} Ò S × ÓÖ ÒØ 4 Ø ÔÓ× Ø Ú ÒÓÖÑ Ð n ÔÓ ÒØ× ÓÙØ Ó Ø Ö ÓÒ V º = S 9 4 ×Ó Ø Ø ÇÖ ÝÓÙ Ó ÒÓØ Ö Ñ Ñ Ö Ø ÓÖÑÙÐ ÓÖ Ø ÚÓÐÙÑ Ó Ò ÐÐ Ô×Ó ¸ Ù× Ò ÝÐ Ò Ö Ð ÓÓÖ Ò √ × x = r cos θ, y = 2r sin θ, z = z, ÝÓÙ Ø Ø 9 dV = 4 V 9 1 4π ( 3 ) = 3π. 4 9 4 2π 0 1 0 1−r 2 0 F · ndS = div FdV = (1 + 1 + 1)dV = 4 V V 9 92 dV = 4 vol(V ) = 4 3 π · 1 · 2 · 1 = 3π. V 2rdrdzdθ = 9 2π 2 4 − 1 (1 − r2 )3/2 3 1 0 = ¾ ÑÖ× Ý Ð ×Ø Ö × ÙÔ ÑÓÙÒØ Ò ÐÓÒ Ø Ô Ø × ÓÛÒ Ò ÙÖ ½º Ì ÖÓÙ ÓÙØ Ø ØÖ Ô Ü ÖØ× ÓÒ× ÖÚ Ø Ú ÓÖ F = (2x + y )i + (x − z sin y )j + (2z + cos y )k Ï Ø × Ø ÛÓÖ a ØÓ ÔÓ ÒØ b ´Ê ÓÒ Ý Ø ÐÐ Ø Ø ÛÓÖ Ý Ð ×Ø Ò ØÖ Ú Ð Ò × C F · dxµ ÖÓÑ ÔÓ ÒØ ÓÖ y = z = 0 Û Ú x2 = 2π, ×Ó x = ÓÖ x = y = 0 Û Ú z = 2π. √ À Ò a = ( 2π, 0, 0), b = (0, 0, 2π). ÆÓÛ¸ Ò Ò ÔÓØ ÒØ Ð ÙÒ Ø ÓÒ Û Ø ∂f ∂x ∂f ∂y √ 2π. = 2x + y ⇒ f (x, y, z ) = x2 + xy + φ(y, z ) = x − z sin y ⇒ x + ∂φ ∂y = x − z sin y ⇒ φ(y, z ) = z cos y + h(z ) ×Ó f (x, y, z ) = x2 + yx + z cos y + h(z ), Ò ∂f ∂z Ò ÐÐÝ = 2z + cos y ⇒ cos y + h (z ) = 2z + cos y ⇒ h(z ) = z 2 + c √ 2 √ Ò C Fdx = [x2 +yx+z cos y +z 2](0,0,π,π),0) = 2π +(2π)2 −( 2π)2 = 4π2 (20 ¿ Ä Ø F : R3 → R3 × Ð Ö ÙÒ Ø ÓÒº ´µ C 2 Ú ØÓÖ Ð Ò Ð Ø f : R3 → R C2 Ñ Ö × ËØ Ø ¸ Ò ÜØ ØÓ ÜÔÖ ×× ÓÒ Û Ø Ö Ø × × Ð Ö ÙÒ Ø ÓÒ¸ Ú ØÓÖ Ð ÓÖ Ñ Ò Ò Ð ×׺ ½º Ö ( Ö f ) Ñ Ò Ò Ð ×× ¾º ÙÖÐ( ÙÖÐF) Ú ØÓÖ Ð ¿º Ú( ÚF) Ñ Ò Ò Ð ×× Ú(F × Ö f ) × Ð Ö ÙÒ Ø ÓÒ º Ö (F( ÙÖÐF)) Ú ØÓÖ Ð º ( Ö f ) × ( ÚF) Ñ Ò Ò Ð ×× ´µ Ñ Ö × ËÙÔÔÓ× ÒÓÛ Ø Ø Ø Ú ØÓÖ Ð F Ò Ø ÒÓÒ¹Þ ÖÓ ÙÒ Ø ÓÒ f × Ø × Ý Ø ÓÒ Ø ÓÒ Ö f × F = 0. ÈÖÓÚ Ø Ø F × ÓÒ× ÖÚ Ø Ú Ò ÓÒÐÝ f F × ÓÒ× ÖÚ Ø Ú º ÖÓÑ Ø ××ÙÑÔØ ÓÒ× Ò Ø Ö Ó Ø ÕÙ ×Ø ÓÒ F Ò f Ö 2 3 Ó Ð ×× C ÓÒ R ´Û Ò Ø¸ Ò Ø × Ô ÖØ Ò ÓÒÐÝ F Ò f ØÓ Ó Ð ×× C 1 ÓÒ R3µ Ë Ò R3 × × ÑÔÐÝ ÓÒÒ Ø ¸ Ø ÓÒ Ø ÓÒ ÓÖ Ú ØÓÖ Ð ØÓ ÓÒ× ÖÚ Ø Ú × Ø Ø Ø ÙÖÐ Ó Ø × Ú ØÓÖ Ð × Þ ÖÓ ´ÓØ Ö Ø ÓÖ Ñ× ÓÖ Ú ØÓÖ Ð ØÓ ÓÒ× ÖÚ Ø Ú Ñ Ý ÕÙÓØ µº ËÙÔÔÓ× Ö×Ø Ø Ø F × ÓÒ× ÖÚ Ø Ú º º ∇ × F = 0, Ø Ò ∇ × (f F) = ∇f × F + f (∇ × F) = ∇f × F + f × 0 = 0 + 0 = 0 × Ò ∇f × F = 0 Ý ××ÙÑÔØ ÓÒ¸ ×Ó f F × ÓÒ× ÖÚ Ø Ú º ÓÖ Ø ÓÒÚ Ö× ¸ ∇ × (f F) Ò ∇f × F = 0, Ø Ò f (∇ × F) = ∇ × (f F) − ∇f × F = 0 − 0 = 0 Ë Ò f × ÒÓÒ¹Þ ÖÓ ÙÒ Ø ÓÒ¸ Û ÓÒ× ÖÚ Ø Ú ¸ ×Ó Û Ö ÓÒ º Ú ØÓ Ú ∇ × F = 0, ×Ó F × ´µ Ñ Ö × Ä Ø S = {(x, y, z ) : x2 + y 2 + z 2 = 2, z ≥ −1} Ò Ð Ø C = Ø× ÓÙÒ ÖÝ ÙÖÚ Ô Ö Ñ ØÖ Þ Ý g(t) = (cos t, sin t, −1), ∂S Ò Ø ËØÓ × Ì ÓÖ Ñ Ù× ØÓ Ò Ø Ú ÐÙ 0 ≤ t ≤ 2π. Ó C Fdx Û Ö F = ∇g Ò g (x, y, z ) = (x2 + y 2 + z 2 )−1/2 ÂÙ×Ø Ý ÝÓÙÖ Ò×Û Öº Ë ÐÐ Ø ××ÙÑÔØ ÓÒ× Ó Ø ËØÓ × Ì ÓÖ Ñ Ö × Ø × S× 1 Ö ÙÐ Ö Û Ø Ô Û × ×ÑÓÓØ ÓÙÒ ÖÝ Ò F × C Ú ØÓÖ Ð ÓÒ ×ÓÑ Ò ÓÖ ÓÓ Ó S Ò R3 ´ ØÙ ÐÐÝ Ø Ú ÐÙ Ó Ø ÒØ Ö Ð × Þ ÖÓµº ´µ Í× Ò ËØÓ × Ì ÓÖ Ñ Û Ú ÙÖÐF = (0, −1, −1) Ò Ø ÙÒ Ø ÒÓÖÑ Ð ØÓ Ø ÔÐ Ò x + z = a ´ Ò Ù Ý Ø ÓÖ ÒØ Ø ÓÒ Ó C µ × 1 1 n = − √2 , 0, √2 ¸ ×Ó I = C ydx + (y 2 + arctan y )dy + (x + 2z )dz = ( ÙÖÐF)ndS = S = S Ñ Ö × Ú ÐÙ Ø C ydx + (y 2 + arctan y )dy + (x + 2z )dz Û Ö C ×Ø ÙÖÚ Ó ÒØ Ö× Ø ÓÒ Ó Ø ×Ô Ö x2 + y 2 + z 2 = a2 Ò Ø ÔÐ Ò x + z = a ÓÖ ÒØ ÐÓ Û × × Ú Û ÖÓÑ ÓÚ º × Ô ÖØ Ó Ø ÔÐ Ò x + z = a Û √ Ò Ø ×Ô Ö x2 + y2√+ z 2 = a2, Ø ×Ó Ø × Ö ÙÐ Ö × Ó Ö Ù× r = 22 a Ò Area(S ) = π( 22 a)2 1 πa À Ò I = √2 π a2 = 2√2 ÆÓØ Ø Ø ×ÓÐÙØ ÓÒ Ó ÐÑÓ×Ø ÒØ Ð ÕÙ ×Ø ÓÒ Ò Ø ×ÓÐÙØ ÓÒ Ñ ÒÙ Ð × ÑÓÖ ÓÑÔÐ Ø º 2 2 S 1 1 (0, −1, −1) · (− √2 , 0, √2 ) = 1 √ 2 S dS = 1 √ Area(S ) 2 ÒØ Ø y , z > 0 Ò× × ρ = x2 + y 2 º 2 ÑÖ× Ñ ×× Ó Ø Ô ÖØ Ó Ø ×ÙÖ z 2 = x2 + 2 2 ÝÐ Ò Ö (x − 1) + y = 1¸ Ø× Ñ ×× Ò× ØÝ D = {(x, y ) : (x − 1)2 + y 2 ≤ 1} = {(r, θ) : − π ≤ θ ≤ π , 0 ≤ r ≤ 2 cos θ} 2 2 m= = S ρ(x, y, z )dS = D x2 + y 2 1 + (√ π π√ √ 3 2 cos θ √ 2 2 x2 + y 2 2dA = − π 0 r 2rdrdθ = − π 2 r3 |2 cos θ dθ = 0 D 2 2 π √π √ √ √ 3 2 2 = 8 2 − π cos3 θdθ = 8 2 sin θ − sin θ π = 8 · 4 2 = 32 2 3 3 3 33 9 2 x )2 x2 +y 2 + (√ y x2 +y 2 )2 dA = ´ÆÓØ Ø Ø (x − 1) + y = 1 Ø Ö × ÑÔÐ ØÖ Ò× ÓÖÑ Ø ÓÒ × x2 + y2 = 2x¸ ×Ó Ù× Ò ÔÓÐ Ö ÓÓÖ Ò Ø × Û Ú r = 2 cos θºµ 2 2 −2 Û× Ñ Ö × ËÙÔÔÓ× Ö ÓÒ D ⊂ R2 × Ö ÙÐ Ö¸ Û Ø Ô ×ÑÓÓØ ÓÙÒ ÖÝ ∂D ÓÖ ÒØ 2 ÓÙÒØ Ö ÐÓ Û × ¸ Ò ×ÙÔÔÓ× 3 Ø Ø (0, 0) ∈ Dint º Ú ÐÙ Ø ∂ D x (ydx−x)2dy º x2 +y 2 ÀÁÆÌ Ö Ò Ø ÓÖ Ñ ÒÒÓØ Ù× ÓÖ D × Ò F ∈ C 1(D)º Ä Ø Ù× Ö ÑÓÚ (0, 0) Ý × D( , 0) Û Ø Ö Ù× ÒØ Ö Ø (0, 0)º ÔÔÐÝ Ò ÒÓÛ Ö Ò³× Ì ÓÖ Ñ ØÓ D\D( , 0) Û Ú D\D 3 ∂ [ −x ] ∂x (x2 +y 2 )2 = 2y ∂ [ (x2x y2 )2 ] ∂y + ¸ ÝÓÙ Ó ÒÓØ Ò ØÓ Ú Ö Ý Ø Øº ( ∂F2 ∂F1 − )dA = ∂x ∂y Fdx + ∂D Fdx, (∂D )− ÛÖ (∂D )− 0 = ∂ D Fdx− ÐÓ Û × ÓÖ ÒØ Ø ÓÒ Ó ∂D . ËÓ Û Ó Ø Ò Fdx, Û Ö ∂D × ÓÖ ÒØ ÓÙÒØ Ö ÐÓ Û × º À Ò ¸ ∂D Ù× Ò Ô Ö Ñ ØÖ Þ Ø ÓÒ x = cos t, y = sin t, 0 ≤ t ≤ 2π ÓÖ ∂D Û Ø Fdx = ∂D ∂D 2π 0 ÒÓØ × Fdx = 2π 0 ( 2 cos2 t)( sin t)(− sin t) − 4 2π 0 3 cos t3 ( cos t) dt = = (− cos2 t sin2 t − cos4 t)dt = − =− 2π 0 cos2 t(sin2 t + cos2 t)dt = 11 ( + cos 2t)dt = −π 22 ...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online